Molecular motifs for additives that retard PEO crystallization - Shrivastava, Sudhakar Dinesh; Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Vanka, Kumar; Kumaraswamy, Guruswamy (Polymer Engineering & Science, 2017)
We investigate the influence of several bifunctional phenol additives (resorcinol: RES, hydroquinone: HYD, p-hydroxybenzoic acid: PHBA, and p-nitrophenol: PNP) on the crystallization of matrix polymer, polyethyleneoxide. We employ solid state Nuclear Magnetic Resonance spectroscopy (NMR), Differential Scanning Calorimetry (DSC), optical microscopy, and Small Angle X-ray Scattering (SAXS) to investigate crystallization of the additivated PEO and compare with Density Functional Theory (DFT) calculations of additive-PEO interactions. Additive-polymer interactions are a function of the functional groups on the additive. Temperature-dependent spherulitic growth rate measurements from optical microscopy and SAXS lamellar long spacings indicate a distinct trend in the effect of additives on PEO crystallization. Change in PEO crystallization is most pronounced with PNP, followed by PHBA and finally RES and HYD. This trend correlates qualitatively with the binding energies of additive-PEO interactions from DFT studies. Our results suggest that DFT calculations might be a useful screening tool to evaluate the influence of additives on polymer crystallization. POLYM. ENG. SCI., 2016. © 2016 Society of Plastics Engineers